Pengaruh Impulsive Buying Tendency terhadap Impulsive Buying, Kepuasan Pelanggan, dan Niat Keberlanjutan dengan Moderasi Stimulus dan Hedonic Motive: Studi pada Pelanggan The Body Shop - Sendy Chandra Kirana; I Made Sukresna (Diponegoro Journal of Management, 2026)
This study is motivated by The Body Shop’s declining performance amid shifting consumer behaviour toward e-commerce platforms. Although known as a pioneer in ethical beauty products, the company faces serious challenges due to its inability to adapt to digital dynamics, particularly in leveraging impulse buying as a sales driver. In this context, impulsive buying behaviour is influenced by the interaction between external stimuli (promotions and app quality) and internal factors such as impulsive buying tendency and hedonistic motives. This study aims to analyse these factors and their impact on customer satisfaction and intention to continue. This study employs a quantitative approach using a survey distributed to 257 student respondents at Diponegoro University who have previously purchased The Body Shop products online. Data analysis employed Structural Equation Modelling (SEM) using AMOS to test causal relationships among variables, including mediation and moderation effects. Validity, reliability, and goodness-of-fit tests were conducted to ensure the model’s suitability. The results of the study indicate that all hypotheses were significantly accepted. Impulsive buying tendency was found to positively affect e-impulsive buying, and this relationship was strengthened by the stimulus. E-impulsive buying positively affects customer satisfaction, which in turn has a very strong effect on the intention to continue. Additionally, the impulsive buying tendency also has a direct effect on customer satisfaction, while the hedonic motive moderates the relationship between e-impulsive buying and customer satisfaction. However, empirical findings indicate low levels of impulsive buying, customer satisfaction, and repurchase intention among The Body Shop consumers, suggesting a failure to establish an optimal chain of impulsive satisfaction. The implications of this study underscore the importance of revitalising digital stimulus strategies, enhancing hedonistic experiences through interactive features, and optimising the impulsive purchasing process to improve customer satisfaction and loyalty. This study also has limitations regarding its single subject and the limited geographical scope of respondents; therefore, future research is recommended to conduct comparative studies, expand the sample, and integrate qualitative approaches to gain a deeper understanding.